Influence of Manufacturing Parameters on Final Quality of Lapped Parts - Stancekova, Dana; Drbul, Mario; Janota, Miroslav; Naprstkova, Natasa; Kulla, Albert; Mrazik, Jozef (Manufacturing Technology Journal, 2016)
For a variety of engineering technologies, machining has a specific position because it is a technology that meets the highest requirements on accuracy and quality of products and involves processes that are final, i.e. the last in the production processes of parts machining. Therefore, these processes largely affects the final shape and dimensional requirements of high quality components and hence their performance characteristics, particularly the accuracy and durability. Such production methods designed to achieve high dimensional and shape accuracy is grinding and other finishing methods (superfinishing, polishing, lapping) involved in a high percentage of the production of components whose quality can not be achieved by other technologies, eventually very difficultly. Lapping and about influence of modification of production parameters on quality of lapped surface after lapping. In the experimental part were taken measurement of roughness parameter Rt. From measured values was evaluated which production parameters are useful and economic preferable by demanded reduction of production time and by keeping the roughness parameter at Rt = 2 μm.
Keywords: lapping; quality; machining; grinding